Woman?s Auxiliary, Officers (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
President MRS. FREDERICK LAIST 24 Tompkins Road Scarsdale, N. Y. First Vice-president MRS. LOUIS D. HUNTOON Pleasantville New York Second Vice-president MRS. REED W. HYDE 84 Mountain Avenue Summit, N. J. Third Vice-president MISS MADELINE P. STONE 49 West 11th St. New York, N. Y. Fourth Vice-president MRS. JOHN J. LINCOLN Elkhorn, McDowell Co. West Virginia